Cultural tourism and city branding in the connected age: the case of cities in Vietnam - Truong, Van-Anh T. (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cultural attractions can help cities get away from a seasonal pattern of tourism, focus on higher-income visitors. Hence, cultural tourism has a strong relationship with city branding. Given a city cannot build separate brands for its different stakeholders, city branding aims to tourists who might be investors or residents in the future. However, the understanding of the searching trend of online travelers is still limited. This study investigates tourism searching patterns and keywords volume related to cultural information through search engines and social media. The research sites include different tourism regions of Vietnam, which are Hanoi, Hue, Danang, Hoi An and Ho Chi Minh. Successful examples of creative cities all over the world are reviewed for technological platform-based communication in three different levels: primary, secondary, and tertiary. The findings show the dominance of central Vietnam cities as a tourism cluster. The study suggests implications for Danang city to use new technologies for city brand communication more effectively.